A new proof of Hartman and Winter's theorem - Develi, Faruk; Celik, Canan (SPRINGER BASEL AG, 2023)
A new proof of Hartman and Winter's theorem (Am. J. Math. 74(4): 834-864, 1952) is presented by using fixed point theory. An illustrative example to this theorem is also given.
Keywords: Partial differential equation; existence of solution; fixed point theory; FIXED-POINT THEOREM; Mathematics